Analyzing the Essence of Stakeholder Relationships: What do we Need in Addition to Power, Legitimacy, and Urgency? - Myllykangas, Päivi (Journal of business ethics, 2011)
This article contributes to the body of stakeholder literature by providing an in-depth analysis of the dynamics of stakeholder relationships as a part of change in value creation. The article presents an argument that the stakeholder salience model as a tool for analyzing stakeholder relationships is not sufficient for understanding business value creation. In the recent stakeholder literature, understanding business value creation has become an important theme. Through an analysis of an empirical case, the article shows how the three stakeholder relationship attributes, legitimacy, power and urgency help to reveal the definitive stakeholders and to capture dynamics of stakeholder relations. However, in the case of strategic change, where the value creation of a firm is in transition, a more profound understanding of stakeholder relationships is needed. As a result of our empirical analysis, six characteristics of stakeholder relationships were identified. To conclude, the question of who and what really counts should be replaced by the question of how value is created in stakeholder relationships.